2020
DOI: 10.1002/biof.1624
|View full text |Cite
|
Sign up to set email alerts
|

6‐Phosphogluconate dehydrogenase fuels multiple aspects of cancer cells: From cancer initiation to metastasis and chemoresistance

Abstract: Reprogrammed metabolism is key biochemical characteristic of malignant cells which represents one of the emerging hallmarks of cancer. Currently, there is rising contemplation on oxidative pentose phosphate pathway (PPP) enzymes as potential therapeutic hits due to their affiliation with tumor metabolism. 6-phosphogluconate dehydrogenase (6PGD), third oxidative decarboxylase of PPP, has received a great deal of attention during recent years due to its critical role in tumorigenesis and redox homeostasis. 6PGD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 81 publications
(84 reference statements)
0
30
0
Order By: Relevance
“…For example, PGD is highly expressed in stage IV LUAD. In addition, many previous studies have demonstrated that overexpression of PGD could lead to cancer metastasis and poor prognosis through diverse mechanisms ( Bechard et al, 2018 ; Sarfraz et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, PGD is highly expressed in stage IV LUAD. In addition, many previous studies have demonstrated that overexpression of PGD could lead to cancer metastasis and poor prognosis through diverse mechanisms ( Bechard et al, 2018 ; Sarfraz et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Although the association between energy metabolism and ferroptosis remains puzzling, Dubreuil et al (2020) have recently discovered that disrupting PPP by PGD knockout inhibits ROS accumulation. Besides, many previous studies have demonstrated that overexpression of PGD could lead to cancer metastasis and poor prognosis ( Bechard et al, 2018 ; Sarfraz et al, 2020 ). In our study, the alteration rate of PGD was more than 1.2% and was related to a significantly poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 PGD is also hyperactive and plays a fundamental role in tumor growth. 49,50 G6PD or PGD depletion significantly decrease NADPH levels and enhance chemotherapeutic drugs-induced cell apoptosis by redox modulation. 51,52 For what concerns activity regulation, NADP + is required for G6PD enzymatic activity, whereas NADPH negatively regulates its activity.…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%
“…Furthermore, Zhang et al established that the TGFβ1-FOXM1-HMGA1-TGFβ1 positive feedback loop maintain G6PD expression in cisplatin resistant cells, and that disruption of this axis sensitizes the cells to the drug [181]. Aberrant expression of 6-phosphogluconate has also been shown to be involved in chemotherapeutic and radiation resistance [182][183][184]. Although preliminary, recent evidence has shown that epidermal growth factor receptor (EGFR) phosphorylates 6PGD at tyrosine (Y481), which enhances 6PGD activity by increasing its affinity to NAD + .…”
Section: Pentose Phosphate Pathwaymentioning
confidence: 99%